Commonwealth Health Ministers' update 2011 (Commonwealth Secretariat LondonGB, 2011)
Outlines examples of responses from member countries, illustrates inherent challenges and demonstrates achievements made from across all sectors to effectively respond to noncommunicable diseases at community, national and international levels.
Keywords: CHRONIC DISEASES